Effect of spironolactone in resistant arterial hypertension: a randomized, double-blind, placebo-controlled trial (ASPIRANT-EXT) - Václavík, Jan; Sedlák, Richard; Jarkovský, Jiří; Kociánová, Eva; Táborský, Miloš (Medicine, 2014)
This study was designed to assess the effect of the addition of low-dose spironolactone on blood pressure (BP) in patients with resistant arterial hypertension. Patients with office systolic blood pressure (SBP) >140 mm Hg or diastolic blood pressure (DBP) >90 mm Hg despite treatment with at least 3 antihypertensive drugs, including a diuretic, were enrolled in this double-blind, placebo-controlled, multicentre trial. One hundred sixty-one patients in outpatient internal medicine departments of 6 hospitals in the Czech Republic were randomly assigned to receive 25 mg of spironolactone (N = 81) or a placebo (N = 80) once daily as an add-on to their antihypertensive medication, using simple randomization. This study was registered with ClinicalTrials.gov, number NCT00524615. A nalyses were done with 150 patients who finished the follow-up (74 in the spironolactone and 76 in the placebo group). At 8 weeks, BP values were decreased more by spironolactone, with differences in mean fall of SBP of -9.8, -13.0, -10.5, and -9.9 mm Hg (P < 0.001 for all) in daytime, nighttime, and 24-hour ambulatory BP monitoring and in the office. The respective DBP differences were -3.2, -6.4, -3.5, and -3.0 mm Hg (P = 0.013, P < 0.001, P = 0.005, and P = 0.003). Adverse events in both groups were comparable. The office SBP goal <14 mm Hg at 8 weeks was reached in 73% of patients using spironolactone and 41% using placebo (P = 0.001). Spironolactone in patients with resistant arterial hypertension leads to a significant decrease of both SBP and DBP and markedly improves BP control.
Keywords: Mineralocorticoid Receptor Antagonists; hypertenze; Female; ženské pohlaví; lidé; dvojitá slepá metoda; krevní tlak; prospektivní studie; Double-Blind Method; Hypertension; Male; Aged; Prospective Studies; lidé středního věku; senioři; mužské pohlaví; Blood Pressure; Spironolactone; spironolakton; Middle Aged; antagonisté mineralokortikoidních receptorů; Humans